THE AFFORDANCES FOR DINING ACTIVITIES: YOUNG GENERATIONS' EXPERIENCE IN DWELLING ENVIRONMENT - Zuhrotul Mawaddatil Ula; Arina Hayati; Sarah Cahyadini (architecture department, Engineering faculty, Universitas Diponegoro, 2022)
Human activities and behavior are reciprocally related to the dwelling environment. As the specific expression of culture, how human activities are carried out is related to how they understand and use the affordances of their environment. One of the primary domestic activities closely related to the culture is dining. Culture influences the dining habits of a community and plays a significant role in the form of dwelling architecture.This study explores how dining activities are carried out in urban housing in Indonesia and their relationship to the dwellings’ architectural forms. Taking Surabaya as a case study, this phenomenon was studied using a combine-strategy through questionnaires and in-depth semi-structured interviews. The participants are the young generation living in their parent’s dwellings with landed housing typology, with and without separate dining rooms. Household members and the dwelling size are not limited to examine how dining activities are conducted in each circumstance.The results show that Indonesian dining culture still influences dining activities in the dwelling. However, dining activities have begun to shift from social to personal activities. The development of a practical lifestyle in recent times has also caused dining activities to be carried out as a complement to other activities. Finally, these phenomena affect the settings and affordance attributes that accommodate dining activities in the dwelling, which understanding can be applied in designing residential architecture.